Government policy and industrial location in South Africa - Bell, Robert Trevor (Rhodes University, Faculty of Commerce, Department of Economics, 1968)
Governments, naturally, pursue social and political as well as economic objectives. The degree to which economic and non-economic objectives harmonise with one another without government interference, however, obviously varies a good deal according to time and place. For instance in the nineteenth century, the priorities of British governments made possible a high degree of individual freedom in the economic sphere. This century, however, as Robbins suggests, has seen a great extension of state activity in the economic sphere, for both economic and non-economic reasons. This tendency, then, is not peculiar to South Africa, but the border industries policy, largely because of its ideological associations and the degree of intervention which it seems to imply, is a particularly controversial example. Chapter 1 para 2.
Keywords: South Africa -- Industries -- Location; Industrial relations -- Government policy -- South Africa